Estudos neutrônicos e termo-hidráulicos para o desenvolvimento de uma metodologia de acoplamento entre códigos aplicada ao reator de pesquisa TRIGA IPR-R1 - Patricia Amelia de Lima Reis (2013)
The computational advances observed in the last two decades have provided direct impact on the researches related to nuclear simulations which use several types of computer codes, including coupled between them, allowing also the analytical simulation and represent with very much accuracy the real behavior of nuclear plants. In this way, studies of complex scenarios in nuclear reactors have been improved by the use of thermal-hydraulic (TH) and neutron kinetics (NK) coupled system codes. This technique consists in incorporating three-dimensional (3D) neutron modeling of the reactor core into system codes, mainly to simulate transients that involve asymmetric core spatial power distributions and strong feedback effects between neutronics and reactor thermal-hydraulics. Therefore, this work presents a series of steps needed to develop a proposal for a methodology of coupling between thermal-hydraulic and neutron kinetics system codes using as a model the research reactor TRIGA IPR-R1. The results obtained are satisfactory and represent important part of the development of this methodology. The codes involved in this work were: RELAP5-MOD3.3, RELAP5-3D 3.0.0, PARCS 2.7 and WIMSD-5B beyond of several graphical interfaces and computational accessory tools